Methodology of Using Innovative Technologies in Teaching Physics in General Education Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Today's modern world is a modern look at every detail in the field of Education encourages to look with. Including each subject in addition to its own teaching methodology, in a way that also embodies modern innovative technologies in it teaching students is one of the pressing issues on the same days. In this article the author details the importance of Physical Science in the world community and the use of innovative technologies in teaching this science to students was.